Penerapan Token Economy untuk Menurunkan Perilaku Agresif pada Anak Usia 6-10 Tahun di Yayasan X - Amalia Mahrunnisa; Aurielle Azzahra; Chaeranny Ratna Syafira Aslam; Agustina Agustina (Lembaga Yasin AlSys, 2026)
Initial observations indicated verbal and physical aggressive behavior among children, such as using harsh language, shouting, disturbing peers, taking belongings without permission, and difficulty following rules. This condition has the potential to hinder children’s social and emotional development, making an intervention appropriate to the developmental characteristics of elementary school age necessary. This study aims to analyze the effectiveness of implementing Token Economy in reducing aggressive behavior among children aged 6–10 years at Foundation X. The intervention was carried out through a positive reinforcement-based Token Economy method using a system of giving tokens in the form of stars, combined with educational activities, group games, and simple rewards as reinforcers of positive behavior. Data were collected through observation, interviews, and pre-test and post-test measurements using the Strengths and Difficulties Questionnaire (SDQ) on the Conduct Problems dimension among six children aged 6–10 years. The results of the program implementation showed a decrease in Conduct Problems scores in five of the six participants, while one participant showed no change because the score had been within the normal range since the initial measurement. The mean Conduct Problems score decreased from 1.67 in the pre-test to 0 in the post-test. The conclusion of the study affirms that the implementation of Token Economy is effective in reducing aggressive behavior and increasing positive behavior among elementary school-aged children. The implications of this study indicate that Token Economy can serve as a simple, practical, and applicable alternative intervention in guiding children’s behavior within the foundation environment.